Recent developments and future prospects on sustainable human resource management: Introduction to the special issue - Ina Ehnert; Wes Harry (Management Revue, 2012)
In this editorial the previous and current state of studies in the subject of sustainability are considered and the role of HRM examined. Particular attention is drawn to the range of definitions of 'sustainability' and to prior approaches to Sustainable HRM. The difficulties of studying the complexities of the topics especially the varying perspectives from geographical locations and from practice and academia are observed. Meanwhile the opportunities for academic research to add value to the world of practice are identified. The editors then outline the contributions by the authors of the three papers and an extended book review that make up the Special Edition. Finally, there are suggestions for the course of future research on this increasingly important topic - for academics, for practitioners and for humanity in general.
Keywords: M12; M14; 650; Human Resource Management; sustainability; Sustainable HRM; literature review